2015
DOI: 10.1016/j.scriptamat.2015.05.011
|View full text |Cite
|
Sign up to set email alerts
|

In situ TEM observations of the lithiation of molybdenum disulfide

Abstract: The lithiation of molybdenum disulfide (MoS 2 ) has been directly studied in situ in the TEM by observing specimens with the viewing direction parallel to the basal planes. The MoS 2 lamella was characterized by bright-field imaging during the lithiation, and both selected-area diffraction and high-resolution imaging before and after. An overall expansion of $5% along the c-direction was observed with concurrent local contraction. The contraction can be related to the expulsion of Mo as Li reduces it to form L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 23 publications
3
24
0
Order By: Relevance
“…This study investigates these mechanisms of lithium intercalation, the role of distribution of intercalated layers, and the formation of dual‐phase 2H‐1T microstructures observed experimentally. As implied by previous experimental studies, and specifically shown by Janish et al, 36 the lithiated 2H phase of MoS 2 can serve as a precursor to obtain the 1T phase during lithiation. In order to gain a mechanistic understanding of lithiation and the phase transformation behavior in thin films of MoS 2 , the energetics of intercalation and the diffusion pathways are first identified in the bulk 2H phase for variations in the concentration of Li, followed by the investigation of the role of Li‐ion concentration and distribution on the 2H‐to‐1T phase transformation behavior.…”
Section: Introductionsupporting
confidence: 56%
See 1 more Smart Citation
“…This study investigates these mechanisms of lithium intercalation, the role of distribution of intercalated layers, and the formation of dual‐phase 2H‐1T microstructures observed experimentally. As implied by previous experimental studies, and specifically shown by Janish et al, 36 the lithiated 2H phase of MoS 2 can serve as a precursor to obtain the 1T phase during lithiation. In order to gain a mechanistic understanding of lithiation and the phase transformation behavior in thin films of MoS 2 , the energetics of intercalation and the diffusion pathways are first identified in the bulk 2H phase for variations in the concentration of Li, followed by the investigation of the role of Li‐ion concentration and distribution on the 2H‐to‐1T phase transformation behavior.…”
Section: Introductionsupporting
confidence: 56%
“…These studies also suggest Li intercalation on monolayer MoS 2 above a concentration of 40% of the available adsorption sites renders a phase transformation from the initial 2H to 1T phase, 31,32 and has also been observed experimentally during Li intercalation 33‐35 . Recent in‐situ lithiation experiments 36 on thin film MoS 2 using high‐resolution transmission electron microscopy (HRTEM) suggest the formation of several thin bands (typically 6‐7 layers) of planar defects. The bands are observed to grow across the sample, parallel to the basal planes, and all of them have approximately the same thickness.…”
Section: Introductionmentioning
confidence: 52%
“…Possible alkali‐metal‐based doping elements on MoS 2 including K and Li are shown in Group IA of Figure .…”
Section: Doping Strategiesmentioning
confidence: 99%
“…Raman spectroscopy is also used to explore the variation in the local structure and oxidation state, as well as the thermal stability of electrode surfaces or electrode-electrolyte interfaces during charge-discharge and heat treatment (Dokko et al, 2002;Hardwick et al, 2008;Membreno et al, 2013;Stancovski and Badilescu, 2013;Wu et al, 2013); FTIR is another effective tool for studying the surface and evolution of electrodeelectrolyte interfaces under cell operating conditions (Aurbach and Chusid, 1997;Chusid et al, 2001;Cheng et al, 2007;Ye et al, 2016). In addition to these spectroscopic techniques, operando SEM (Miller et al, 2013;Hovington et al, 2014;Marceau et al, 2016) and TEM (Liu, S. et al, 2014;Janish and Carter, 2015;Wang, 2015;Chen et al, 2016a;Xu et al, 2016) show the evolution of direct images of cycling electrode at the micro-and nano-scales. By combining the images with energy dispersive X-ray spectroscopy, electron energy loss spectroscopy and electron diffraction, the information on particle morphology, crystal structure, phase transformation, multi-phase interface behavior, element distribution and element positions are obtained as a function of the electrochemical process.…”
Section: Introductionmentioning
confidence: 99%